Posttransplant de novo DSA and NDSA affect GvHD, OS, and DFS after haplo-HSCT in patients without pre-existing HLA antibodies of hematological malignancies - Wang, Lan; Ji, Kai; Chen, Luyao; Li, Ying; Zhu, Wenjuan; Yuan, Xiaoni; Bao, Xiaojing; Wu, Xiaojin; He, Jun (Frontiers in Immunology, 2022)
To examine the production time, type, and MFI of post-transplantation de novo HLA antibodies, and their effects on haplo-HSCT outcomes, we retrospectively included 116 patients who were negative for pre-existing HLA antibodies. In total, 322 serum samples from pre-transplantation to post-transplantation were dynamically tested by Luminex and single-antigen bead reagents. Patients were divided into: HLA antibody persistently negative group (group 1), the de novo HLA antibody transiently positive group (group 2), the de novo HLA antibody non-persistently positive group (group 3), and the de novo HLA antibody persistently positive group (group 4). Group 4 included DSA+non-DSA (NDSA) (group 4a) and NDSA (group 4b) groups. The detection rate of de novo HLA antibodies was 75.9% (88/116). The median MFI for de novo HLA antibodies was 2439 (1033-20162). The incidence of II–IV aGvHD was higher in group 2 than in group 1 (52.6% vs 17.9%, P < 0.01); in group 4a than in group 1 (87.5% vs 17.9%, P < 0.001); and in group 4a than in group 4b (87.5% vs 40.0%, P = 0.001). The DFS (37.5% vs 85.7%, P < 0.01) and OS (37.5% vs 85.7%, P < 0.01) of group 4a were lower than those of group 1. The DFS (48.0% vs 85.7%, P < 0.01) and OS (56.0% vs 85.7%, P = 0.03) of group 4b were lower than those of group 1. Multivariate analysis showed that de novo HLA antibody being transiently positive (HR: 5.30; 95% CI: 1.71–16.42, P = 0.01) and persistently positive (HR: 5.67; 95% CI: 2.00–16.08, P < 0.01) were both associated with a higher incidence of II–IV aGvHD. Persistently positive de novo HLA antibodies were a risk factor for reduced DFS (HR: 6.57; 95% CI: 2.08–20.70, P < 0.01) and OS (HR: 5.51; 95% CI: 1.73–17.53, P < 0.01). DSA and NDSA can be detected since 15 days after haplo-HSCT in patients without pre-existing HLA antibodies, and affect aGvHD, DFS, and OS. Haplo-HSCT patients must be monitored for HLA antibodies changes for appropriate preventive clinical management, and we recommend that 1-month post-transplantation is the best test time point.